Identification and geochemical modeling of processes controlling leaching of Cr(VI) and other major elements from chromite ore processing residue - Geelhoed, Jeanine S; Meeussen, Johannes C.L; Hillier, Stephen; Lumsdon, David G; Thomas, Rhodri P; Farmer, John G; Paterson, Edward (Geochimica et cosmochimica acta, 2002)
Chromite ore processing residue (COPR) contains very high levels of chromium as Cr(III) and Cr(VI) and has a pH of ∼11.5 to 12. Millions of tonnes of COPR have in the past been deposited in urban areas. We have studied the factors that control leaching of Cr(VI), Ca, Al, Si, and Mg from COPR by means of batch experiments, mineralogical characterization of COPR via X-ray powder diffraction and scanning electron microscopy, and chemical equilibrium modeling. Batch experiments at a range of pH values and two liquid:solid ratios showed that mineral solubility control exists for aqueous concentrations of Cr(VI) above pH 10. Calculations indicate that the solid phases that control the solubility of Cr(VI) at pH values above 11 are Cr(VI)-substituted hydrogarnet (Ca 3Al 2(H 4O 4,CrO 4) 3) and Cr(VI)-hydrocalumite (Ca 4Al 2(OH) 12CrO 4·6 H 2O), a layered double-hydroxide clay with chromate anions held in the interlayers. In the pH range 9.5 to 11, the description of the Cr(VI) concentration in solution was strongly improved by the incorporation in the model of Cr(VI)-ettringite (Ca 6Al 2(OH) 12(CrO 4) 3·26 H 2O), which precipitates as a secondary phase when hydrocalumite dissolves. The proposed model for leaching of COPR at high pH includes Cr(VI)-bearing hydrogarnet, Cr(VI)-hydrocalumite, Cr(VI)-ettringite, brucite, calcite, Ca 2Al 2(OH) 10·3 H 2O, CaH 2SiO 4, and gehlenite hydrate (Ca 2Al 2(OH) 6SiO 8H 8·H 2O). The model accurately predicts the concentrations of Cr(VI), Ca, Al, Si, and Mg in solution in the pH range 10 to 12 as well as the pH-buffering behavior. Below pH 8, a decrease in the Cr(VI) concentration in solution is observed, which may be attributed to sorption of chromate onto freshly precipitated Al and Fe hydroxide surfaces. Sulfate and carbonate show the same type of behavior as chromate. The chemistry of COPR shows similarities with cement and high-pH municipal waste incinerator bottom ash.